PENGARUH OLAHAN ORGANIK JERAMI DAN JARAK TANAM SISTEM JAJAR LEGOWO TERHADAP PRODUKSI TANAMAN PADI (Oryza sativa L.) - Istiqomah Istiqomah; Alfin Wahyudin; Choirul Anam (AGRORADIX : Jurnal Ilmu Pertanian, 2021)
Rice has become an important and strategic commodity. The decline in soil fertility is the cause of the low production of rice plants.The use of straw can increase the efficiency of the use of fertilizers (nitrogen), improve soil fertility by providing nutrients, especially (potassium), besides that it can improve the soil. The nutrient content of rice straw is 0.4% Nitrogen, 0.02% Phosphorus, 1.4% Potassium and 5.0% Silicon. The jajar legowo planting system is a new innovation in agriculture.This study aims to determine the best spacing between 2:1 and 4:1 jajar legowo system and to find out the best quality of processed straw from bokashi straw and burnt straw. This research was conducted in Pelangwot village, Laren sub-district, Lamongan district. January to April 2021. This research was conducted using a factorial randomized block design (RAK) method, which consisted of two factors and each factor consisted of 3 levels. From these two factors, 9 treatment combinations were obtained and repeated 3 times. Parameters observed in the vegetative phase include: plant height and number of leaves. Parameters observed in the generative phase include: wet weight of plants, panicle length. dry seed weight, dry seed weight per plot, 1000 seed weight The data obtained from the observations were calculated by analysis of variance with Fisher's exact test (F test at 5% and 1 level). If there is a significant difference, it will be continued with the Least Significant Difference test. The best results in this study were burnt straw treatment and 4:1 row spacing legowo